Óleo essencial e infusão de Aloysia triphylla: efeitos na estabilidade da carne de jundiá (Rhamdia quelen) - Daniel, Ana Paula (2014)
This study has aimed to evaluate the effects of treatments with essential oil (OAT) and infusion of Aloysia triphylla (IAT) on microbiological, chemical and sensory stability of silver catfish (Rhamdia quelen). α-citral (29.4%) and β-citral (20.8%) were the main components of OAT, followed by limonene (11.9%). Major compounds identified in the IAT were isoquercetrin > rosmarinic acid > luteolin. Experiments were divided in four parts in which the first has was aimed at evaluating the antimicrobial activity of OAT against foodborne bacteria strains, the microbiological stability of silver catfish fillets refrigerated after dipping in OAT solution and the microbiological changes during the ice storage of whole silver catfish previously sedated with OAT during the transport in vivo. In vitro assays revealed that the OAT has strong inhibitory activity against Staphylococcus aureus and Enterococcus faecalis, and moderate inhibitory activity against Escherichia coli, Enterobacter aerogenes, Salmonella Typhimurium, Salmonella Choleraesuis and Salmonella Enteritidis, but does not inhibit Pseudomonas aeruginosa. Fillets imersed in 30 or 40 μL/L of OAT had lower mesophilic and psychrotrophic counts than control (p<0.05) during storage. Entire refrigerat fish that were previously sedated with 40 μL/L of OAT slowed lower counts for psychrotrophic at the 7th and 28th days of storage than control (p<0.05), whereas the mesophilic counts were similar to the control during storage. The 2nd experiment has aimed at determine whether the use of OAT in the water (0, 30 or 40 μL/L) to sedate silver catfish during transport action would delay the chemical and the sensory post mortem changes of refrigerated whole fish. Fresheness of entire silver catfish was extented by sedation with 40 μL/L of OAT as indicated by the delay in the onset of rigor mortis and in the degradation of inosine 5'-monophosphate into inosine compared to the control (p<0.05). Fish exposed to 30 or 40 μL/L OAT received lower demerit scores than the control (p <0.05) in sensory evaluation after 10 days of storage, whereas fish treated with 40 μL/L of OAT had higher shelf life (35 days in ice) than the control (p<0.05). In the 3rd experiment, we assessed whether the use of OAT in the water to sedate silver catfish during transport would influence the lipid stability of fish fillets during frozen storage (17 months). The fillets from fish exposed to 30 and 40 μL/L of OAT had higher initial content of primary products of lipid oxidation (conjugated dienes, CD) than control fillets, whereas the fillets from fish exposed to 40 μL/L of OAT had lower content of secondary products of lipid oxidation (thiobarbituric acid reactive substances, TBARS) after 6, 9 and 17 months of frozen storage than control fillets (p<0.05). The 4th experiment was aimed at evaluating the in vitro antioxidant activity of IAT and the lipid stability and instrumental color of frozen fillets after immersion in distilled water (control) or IAT (1, 2.5 or 5%). The antioxidant effect of IAT (1-5%) was demonstrated as the treated fillets had lower CD values after 7 months of storage, as well as lower TBARS value than control after 4, 7 and 10 months of storage. Regardeless of the storage time, the treatment with 5% IAT reduced brightness, increased the yellowness and chroma compared to control fillets, whereas the treatment with 2.5% IAT only increased the yellowness. However, the total color change during the storage of fillets treated with 2.5 and 5% IAT was lower than in control fillets (p <0.05). These results indicate that OAT has antimicrobial activity against foodborne bacteria. Furthermore, the use of OAT as a sedative in the transport of silver catfish extended the freshness and increased shelf life of the refrigerated whole fish, and also delayed lipid oxidation of the fillets during frozen storage. Dipping silver catfish fillets in IAT delayed lipid oxidation and color changes during frozen storage, which can extend the shelf life of fillets. These results indicate the great potential of A. triphylla in the fish processing sector as a pre-slaughter treatment (sedative) or in the post-slaughter period (natural food additive).